2003
DOI: 10.1029/2003gl017686
|View full text |Cite
|
Sign up to set email alerts
|

Elastic thickness and isostatic coherence anisotropy in the South Indian Peninsular Shield and its implications

Abstract: [1] We present measurements of the mechanical strength of the lithosphere of the South Indian Peninsular Shield (SIPS). Values of Effective Elastic Thickness (Te) were obtained from azimuthally averaged coherence measurements g 2 (jkj) between Bouguer gravity and topography using a multitaper method (MTM) and a mirrored periodogram method (MPM). Values of Te from MTM (11 -16 km) are consistently lower than those from MPM (20-31 km) and are contained within the seismogenic thickness (Ts), substantiating earlier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 16 publications
1
5
1
Order By: Relevance
“…In addition, directions aligned with significant anisotropy in the topography or gravity data may also be spurious. A conservative global reanalysis of gravity-topography coherence on these terms, which we present in the Supplementary Material, produces only scant evidence for lithospheric flexural anisotropy, in marked contrast to previous results (Rajesh et al, 2003;Stephen et al, 2003;Nair et al, 2011Nair et al, , 2012Zamani et al, 2013). We draw attention particularly to the results reported by Audet and Bürgmann (2011), which we feel are in danger of being over-interpreted.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…In addition, directions aligned with significant anisotropy in the topography or gravity data may also be spurious. A conservative global reanalysis of gravity-topography coherence on these terms, which we present in the Supplementary Material, produces only scant evidence for lithospheric flexural anisotropy, in marked contrast to previous results (Rajesh et al, 2003;Stephen et al, 2003;Nair et al, 2011Nair et al, , 2012Zamani et al, 2013). We draw attention particularly to the results reported by Audet and Bürgmann (2011), which we feel are in danger of being over-interpreted.…”
Section: Discussioncontrasting
confidence: 52%
“…First applied to the Australian continent and the Canadian Shield, these methods have since yielded apparent evidence for pervasive mechanical anisotropy worldwide (Rajesh et al, 2003;Stephen et al, 2003;Nair et al, 2011Nair et al, , 2012Zamani et al, 2013). Audet and Bürgmann (2011) made a geologically attractive case for tectonic inheritance being a controlling factor in the deformation behaviour of the lithosphere throughout supercontinent cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Authors using mirroring with Fourier-based coherence methods, such as periodogram, maximum entropy and multitaper methods, have reported that the recovered T e is usually overestimated when mirroring is performed [e.g., Lowry and Smith, 1994;Ojeda and Whitman, 2002;Stephen et al, 2003]. The mirroring introduces artificial long-wavelength signals into the data, which have the effect of shifting the coherence transition to smaller wave numbers [Lowry and Smith, 1994;McKenzie and Fairhead, 1997;Ojeda and Whitman, 2002].…”
Section: Effect Of Mirroringmentioning
confidence: 99%
“…[36] The preprocessing technique of mirroring the gravity/topography data before performing a Fourier transform has been performed in many studies [e.g., Zuber et al, 1989;Lowry and Smith, 1994;Macario et al, 1995;Hartley et al, 1996;McKenzie and Fairhead, 1997;Poudjom Djomani et al, 1999;Ojeda and Whitman, 2002;Stephen et al, 2003;Stark et al, 2003]. Authors using mirroring with Fourier-based coherence methods, such as periodogram, maximum entropy and multitaper methods, have reported that the recovered T e is usually overestimated when mirroring is performed [e.g., Lowry and Smith, 1994;Ojeda and Whitman, 2002;Stephen et al, 2003].…”
Section: Effect Of Mirroringmentioning
confidence: 99%
“…Using two different window sizes, we ensured that window size does not affect the Te values to any considerable extent. For example, Stephen and Singh (2003) used MTM spectral analysis for estimating Te in the south Indian shield. They used window sizes of 450×450 km 2 , 620×620 km 2 and 750×750 km 2 .…”
Section: Resultsmentioning
confidence: 99%